Lactobacillus rhamnosus GG (ATCC 53103) for the Management of Infantile Colic: A Randomized Controlled Trial - Savino, Francesco; Montanari, Paola; Galliano, Ilaria; Daprà, Valentina; Bergallo, Massimiliano (Nutrients, 2020)
Background: The aim of this study was to investigate the efficacy of Lactobacillus rhamnosus ATCC 53103 together with the maternal diet avoidance of cow’s milk in treating infantile colic. Methods: Forty-five colicky breastfed infants were consecutively randomized to receive L. rhamnosus for 28 days at a dosage of 5 × 109 cfu per day or placebo. Faecal samples were collected from each subject before starting supplementation and at the end of the study period and were immediately analysed. Faecal calprotectin was detected via a quantitative assay. The total bacterial load and selected bacterial species were evaluated using real-time TaqMan PCR. Results: After supplementation for 28 days with Lactobacillus rhamnosus ATCC 53103, median full-force daily crying was reduced (104 versus 242 min, p < 0.001) and the values of faecal calprotectin decreased significantly (p = 0.026). Furthermore, the probiotic increased the abundance of Lactobacillus (p = 0.048) and total bacteria (p = 0.040); all these effects were not observed in the placebo group. Conclusion: Infants treated with Lactobacillus rhamnosus ATCC 53103 for 28 days, in association with the elimination of cow’s milk from the maternal diet, presented some interesting features related to the effect of this probiotic treatment: reductions in crying time and faecal calprotectin, with increased total bacteria and Lactobacillus. To validate these results, a double-blind, placebo-controlled trial on a larger cohort is required.